Social Media Use and Children's Wellbeing - Emily McDool; Philip Powell; Jennifer Roberts; Karl Taylor (Institute of Labor Economics (IZA), 2016)
Childhood circumstances and behaviours have been shown to have important persistent effects in later life. One aspect of childhood that has changed dramatically in the past decade, and is causing concern among policy makers and other bodies responsible for safeguarding children, is the advent of social media, or online social networking. This research explores the effect of children's digital social networking on their subjective wellbeing. We use a large representative sample of 10-15 year olds over the period 2010 to 2014 from the UK Household Longitudinal Study, and estimate the effect of time spent chatting on social websites on a number of outcomes which reflect how these children feel about different aspects of their life, specifically: school work; appearance; family; friends; school attended; and life as a whole. We deal with the potential endogeneity of social networking via an instrumental variables approach using information on broadband speeds and mobile phone signal strength published by Ofcom. Our results suggest that spending more time on social networks reduces the satisfaction that children feel with all aspects of their lives, except for their friendships; and that girls suffer more adverse effects than boys. As well as addressing policy makers' concerns about the effects of digital technology on children, this work also contributes to wider debates about the socioeconomic consequences of the internet and digital technologies more generally, a debate which to date has largely been based on evidence from outside of the UK.
Keywords: D60; I31; J13; 330; digital society; social media; wellbeing; children